206k views
3 votes
Y=-x^2+12x-4Complete the square for - x^2+12x-4Use ax^2+bx+cA=-1, b=12, c=-4

User Nisala
by
5.3k points

1 Answer

4 votes

The given equation is


y=-x^2+12x-4

To complete the square take -1 as a common factor from the right side


-x^2+12x-4=-1(x^2-12x+4)

Divide the term of x by 2 to find the product of the first and second terms in the bracket


(-12x)/(2)=-6x

The bracket will be (x - 6)

Square it


(x-6)^2=x^2-12x+36

Then add and subtract (36 - 4)


-\lbrack(x^2-12x+4+32)-32\rbrack=-(x^2-12x+36)+32

Make the trinomial a square binomial


-(x^2-12x+36)-32=-(x-6)^2+32

The completing square is


-x^2+12x-4=-(x-6)^2+32

User Marco Pace
by
5.8k points